2014
DOI: 10.4103/0974-8237.135216
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral atlanto-axial fractures in near side impact collisions: An under recognized entity in cervical trauma

Abstract: Objective:Nearside impact collisions presenting with lateral mass fractures of atlanto-axial vertebrae contralateral to the impact site represents a rare fracture pattern that does not correlate with previously described injury mechanism. We describe our clinical experience with such fractures and propose a novel description of biomechanical forces involved in this unique injury pattern. The findings serve to alert clinicians to potentially serious consequences of associated unrecognized and untreated vertebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Case reports and retrospective reviews of routinely collected data of severe spinal injury following an MVC featured both adults and children [52][53][54][55][56]. Mezue et al reported failures in prehospital immobilisation and careful handling in patients with subsequently proven spinal cord injury [57].…”
Section: Spinal Injuriesmentioning
confidence: 99%
“…Case reports and retrospective reviews of routinely collected data of severe spinal injury following an MVC featured both adults and children [52][53][54][55][56]. Mezue et al reported failures in prehospital immobilisation and careful handling in patients with subsequently proven spinal cord injury [57].…”
Section: Spinal Injuriesmentioning
confidence: 99%